PENGELOLAAN SISTEM KREDIT EKSTRA KURIKULER DI STAIN PAMEKASAN - Buna'i Buna'i (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
This research based article is trying to describe the teaching and learning management in the Excellent Class of STAIN Pamekasan. There are 4 focuses of this research, they are: (1) why does STAIN Pamekasan apply the credit system of extracurricular? (2) How is the application of the credit system of extracurricular? (3) What are the academic advising lecturer’s roles in the credit system of extracurricular in STAIN Pamekasan? (4) How are the organization of university students’ roles in the credit system of extracurricular to the activity of students of STAIN Pamekasan? The purpose of this study is to describe and explain about: (1) the reasons of the application of credit system of extracurricular, (2) the ways how the credit system is applied in STAIN Pamekasan, (3) the academic advising lecturers’ role in applying the credit system of extracurricular in STAIN Pamekasan, (4) the roles of students’ organization in credit system of extracurricular to the students’ of STAIN Pamekasan activity.